(untitled) (EAAE Annual Conference Proceedings, 2024)
Transforming urban environments in relation to sustainability and sufficiency requires developing, through an interdisciplinary approach, methodologies and tools for evaluating and valorizing certain abandoned spaces in the city: for example, areas in disuse linked to pre-existing military complexes that have significant dimensions and strategic positions. In their interactions with territorial structures, military areas often reveal their links with networks that have characterized their transformation over time, due to historical strategic and military assets that have defined their urban form. A case study in Bologna was conducted within a research project (The architectural design process in the digital transition. An interdisciplinary approach to the evaluation and valorization of “discarded” spaces in cities. FIRD 2023 Department of Architecture University of Ferrara, Principal Investigator A. Massarente, with K. Cavallari, G. Emmi, C. Erdmann Goldoni, E. Guidetti, A. Gaiani, M. Patamia, V. Radi, A. Tessari, 2023-2024). It was complemented by teaching activity, based on which we will develop possible different urban regeneration strategies leading to new scenarios.